Exploring church history - Vos, Howard Frederic, 1925- (Nashville, TN Thomas Nelson, 1994)
Includes bibliographcial references and index.
Originally published as : Introduction to Church history, 1994 in series Nelson's quick reference.
Keywords: Chirch history -- introductions